Trans‐seasonal activation of the neuroendocrine reproductive axis: Low‐temperature winter dormancy modulates gonadotropin‐releasing hormone neurons in garter snakes. Issue 1 (16th July 2021) - Lutterschmidt, Deborah I.; Lucas, Ashley R.; Summers, Andrew R.
Abstract: All animals use external cues from the environment to accurately time life‐history events. How the brain decodes environmental stimuli to effect changes in physiology and behavior, however, is poorly understood, particularly with regard to supplementary environmental cues such as temperature. We asked if low‐temperature dormancy alters the synthesis and/or release of gonadotropin‐releasing hormone (GnRH). We used the well‐studied red‐sided garter snake ( Thamnophis sirtalis ) for this study, as low‐temperature exposure is both necessary and sufficient to induce reproduction in northern populations of this species. Snakes were collected from the field and hibernated at 4°C or 10°C in complete darkness for up to 16 weeks. In males, increasing duration of low‐temperature dormancy significantly increased GnRH‐immunoreactive cell number and GnRH soma size (a proxy for relative cell activity) in the forebrain. These changes mirrored those in male reproductive behavior (reported previously) and plasma androgen concentrations. The changes in GnRH cell area observed in males were specific to the neuroendocrine population of cells in the medial preoptic area; soma size in the rostral GnRH cells did not change. Finally, temperature‐induced changes in GnRH were sexually dimorphic: neither hibernation temperature nor the duration of winter dormancy significantly modulated GnRH cell number or soma size in females, despite the fact that plasma estradiol and corticosterone increased significantly in response to both. These data demonstrate that the neuroendocrine GnRH system is sensitive to environmental temperature and suggest that GnRH neurons play a conserved but trans‐seasonal role in mediating changes in reproductive physiology and behavior in dissociated breeders. Abstract : Northern populations of red‐sided garter snakes ( Thamnophis sirtalis parietalis ) hibernate in underground dens at low temperatures for 8 months each year and breed in the spring. Although these snakes are dissociated breeders, 8 weeks of low‐temperature dormancy significantly increased both the number and size of neurons positively labeled for gonadotropin‐releasing hormone (GnRH) in the hypothalamus and significantly modulated plasma sex steroid hormones. Changes in GnRH immunoreactivity were sexually dimorphic. These findings reveal that environmental temperature can modify the activity of the neuroendocrine reproductive axis, an effect that is likely applicable to all vertebrates and relevant to understanding how climate change may impact reproductive timing. Research Highlights: Low‐temperature winter dormancy increases GnRH‐immunoreactive cell number and soma size in male red‐sided garter snakes, a dissociated breeder that exhibits temperature refractoriness. Responses of GnRH neurons varied with both sex and topography.